Facial plexiform neurofibroma in a child with neurofibromatosis type I: A case report - Patil K; Mahima V; Shetty S; Lahari K (Wolters Kluwer Medknow Publications, 2007)
Plexiform neurofibroma is a non-circumscribed, thick, and irregular benign tumor of the peripheral nerve sheath. It is a virtually pathognomonic and often disabling feature of neurofibromatosis type I. The diffuse and soft nature of plexiform neurofibroma is often compared to ′a bag of worms′ and is difficult to distinguish from a vascular malformation or a lymphangioma, thus necessitating thorough clinical and histopathological examination and imaging of the lesion. We present a case of plexiform neurofibroma in a 12-year-old male child.